ROLE OF THE MODULATORY MEDIATOR SEROTONIN IN THE INDUCTION OF EPIGENETIC PROCESSES DURING LONG TERM MEMORY FORMATION IN HELIX - L. N. Grinkevich; O. V. Vorobiova (Вавиловский журнал генетики и селекции)
Epigenetic mechanisms controlling long-term memory formation are a promising field in neurobiology. They include posttraslational histone modifications, which lead to chromatin remodeling and thereby influences gene expression involved in learning. Mollusks are a popular model in neurobiology, because they have relatively simple CNSs with giant neurons. Previously, we found strong induction of histone H3 acetylation and methylation during food aversion conditioning in Helix. We think that these processes are regulated by modulatory mediator serotonin, playing an important role in avoidance behavior. To study the influence of serotonin on induction of epigenetic processes, we investigated the action of an unselective antagonist of serotonin receptors, metitepine, on the acetylation and methylation of histone H3 during Helix learning. We found that metitepine treatment prevented activation of methylation and acetylation of H3 induced by learning in the CNS of the snail and deteriorates long term memory formation. Long-term memory formation in metitepine-treated animals can be improved by treatment with histone deacetylase inhibitor Na В. Our data confirm the important role of serotonin in the induction of epigenetic processes during aversion conditioning in Helix.